Pengaruh Pakan Sintasan Benih Ikan Kerapu Cantang (Epinephelus Fuscoguttatus X Epinephelus Lanceolatus) Di Situbondo Jawa Timur - Catur Pramono Adi; Marzuki Marzuki; Aripudin Aripudin; Guntur Prabowo (Universitas Mataram, 2024)
Fish growth is one of the problems faced by many grouper fish farmers, where this problem requires a large amount of money. The problem with growth is the lack of feed needed to increase protein for the growth of grouper fish. The aim of carrying out this research is: To determine the effect of feed on the survival of Cantang Grouper. The results of the research show that in providing feed at CV. Jaya Utama Abadi suits the nutritional needs of grouper fish, from natural food to artificial food. Natural food in the form of phytoplanton and zooplanton. The type of phytoplanton used is Chorella sp. and for zooplanton there are two types, namely Rotifera sp. and Artemia. The planton is cultured itself starting from fertilization, hatching, and harvesting. Butane feeding is also supplemented with rebon shrimp